Hiking the road to ruins day trips and camping adventures to iron mines, old military sites, and things abandoned in the New York City area-- and beyond - Steinberg, David A. (Rivergate regionals., 2015)
"In this easy to use, informative, and occasionally eccentric guidebook, David A. Steinberg blazes the trail to more than twenty-five unusual landmarks and hard-to-find destinations that are mostly within a two-hour drive of New York City. Suitable for the experienced hiker or camping adventurer--as well as anyone that has the desire to explore--Hiking the Road to Ruins has been updated to include detailed directions and GPS coordinates to specific sites as well as many new hikes"--